Preservasi Digital sebagai Upaya Akuntabilitas Tata Kelola Arsip di Lembaga Kearsipan di Indonesia - Nurdiansyah, Aulia; Valentino, Rahmat Aliﬁn; Yussuf, Salaisyah Amalia (Khazanah: Jurnal Pengembangan Kearsipan, 2025)
The purpose of this study is to examine the implementation of digital archive preservation in ANRI Award-winning institutions, namely the Library and Archives Service of the Special Region of Yogyakarta, Central Java Province, and West Java Province, which focuses on (1) migration methods, (2) conversion methods, (3) encapsulation methods, (4) emulation methods, (5) replication methods, and (6) refreshing methods in efforts to preserve digital archives. In addition, the strategies of these institutions in obtaining the ANRI Award were also studied. The research method used was a case study with a qualitative approach. The data collection method used observation, interviews, and documentation to obtain comprehensive data. Then the data were analyzed through the stages of data reduction, data presentation, and drawing conclusions, and to test the validity of the data, a validity test was carried out using the triangulation technique. The results of the study showed that the implementation of six digital archive preservation methods had been applied in these archival institutions. The intensity of the application of the conversion, migration, encapsulation, and replication methods were quite high compared to the emulation and refreshing methods. The difference in the application of digital archive preservation lies in the hardware and software used. These archival institutions need to improve hardware with speciﬁcations to support emulation activities and add human resources in refreshing activities. This research is expected can become an evaluation for these archival institutions and a reference for other archival institutions related to digital archive preservation activities.